Macbeth's Banquo: Faux Ami as Christian Friend - Fendt, Gene (Literature and theology, 2009)
One sign of Banquo's nature and authorial intent regarding Macbeth is what we might call Banquo's grammar. In grammar, a faux ami is a word in a foreign language that looks like a word in one's own, but means something quite different. Banquo is the ghost of such a word. In Latin, he would be declined banquo, banques, banquet; but the word does not exist in Latin. So ‘Banquo’ is the ghost of a faux ami; his being and ghost a double edged grammatical pun. His appearance and action at Macbeth's banquets (where Macbeth performs ‘non banquo’) exhibit that he is, moreover, the truest friend.